Peningkatan Pengetahuan Keagamaan Masyarakat Desa Tanakaraeng Melalui Kegiatan Pelatihan Penyelengaraan Jenazah - Muh Zainal Izulhaq Zhainal; Muh Ihza Mahendra Ihza; Nur Khotimah Husnah Titi; Aufa Hudzaifah; Nur Indah Ramadhani; Shafirah Aprilia Putri; Marwah Nurhudaya; Nurinayah Anwar; Fitra Amalia Jafar; Kusnadi Umar (Pangulu Abdi: Jurnal Pengabdian Kepada Masyarakat, 2022)
In Islamic teachings there are several main things that are required to be carried out as soon as possible, namely paying debts, marrying off girls if they meet the requirements and have asked to be married, and finally organizing a funeral for fellow Muslims. The importance of this training is to educate the public regarding the procedures for caring for corpses, because in this modern era these kinds of religious activities have begun to be abandoned. The purpose of conducting this research is to find out the procedure for organizing corpses, as well as it is hoped that this research can later become additional knowledge for the wider community and become an additional reference for further research. The research method used in this research is field or qualitative research using a descriptive analysis approach. In this study it can be concluded that in general the people in Tanakaraeng Village still do not understand or do not understand the procedures for organizing corpses. In general, what has happened in the Tanakaraeng Village community so far is that only certain people who act as caretakers have been appointed as caretakers. This happened due to the lack of public knowledge regarding the procedures for organizing corpses. Keywords: Bodies, Community, Training